2020
DOI: 10.28940/terra.v38i3.656
|View full text |Cite
|
Sign up to set email alerts
|

Respuesta del cultivo de maíz a la bio-inoculación y fertilización química reducida en campo

Abstract: El efecto de los microorganismos del suelo suele ser de gran transcendencia ecológica y económica en los sistemas de producción agrícola. Por ello se estimó la respuesta agrobiológica de la inoculación o coinoculación de hongos micorrízicos arbusculares (HMA), rizobacterias (Azospirillum brasilense, Ab) y dosis reducida de fertilizante inorgánico (FI) en el cultivo de maíz (Zea mays L.) en campo. El experimento se realizó en el campo experimental “La Bandera” ubicado en el municipio de Actopan, Veracruz, Méxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
4
0
2
Order By: Relevance
“…In this sense, the presence of organic matter in the soil and its degradation by microorganisms allowed for adequate nutritional and moisture retention conditions, which is reflected in the height reached by the plants of treatments T7, T6 and T5. In this regard, it was reported that, for the roots of the corn plants that were not inoculated with microorganisms, a root colonization of 7.83% was observed from native soil mycorrhization [ 67 ]. Organic fertilizers provide organic matter, nutrients and additional microorganisms that favor soil fertility and the subsequent nutrition of crops [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the presence of organic matter in the soil and its degradation by microorganisms allowed for adequate nutritional and moisture retention conditions, which is reflected in the height reached by the plants of treatments T7, T6 and T5. In this regard, it was reported that, for the roots of the corn plants that were not inoculated with microorganisms, a root colonization of 7.83% was observed from native soil mycorrhization [ 67 ]. Organic fertilizers provide organic matter, nutrients and additional microorganisms that favor soil fertility and the subsequent nutrition of crops [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results are similar to those obtained for the other plants of the Kculli race cultivated in Peru, with stem diameters of 2.05 to 2.27 cm [ 73 ]. In this regard, bioinoculants together with the contribution of chemical fertilizer result in an increase in the plant stem diameter [ 40 , 67 ]. Slightly lower results were recorded in treatments T3, T4, T5 and T6 with values of 1.94, 1.89, 1.87 and 1.83 cm of stem diameter, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Creole corn (olotillo race) exceeded the plant height in comparison to the C/Acceleron A7573 hybrid genotype. Authors like Zulueta-Rodríguez et al (2020) showed statistical significance in plant height after confirming notable differences in their treatments with A. brasilense, catalogued as PGPB with great impact within sustainable agriculture due to the multiple promotion mechanisms attributed to them. However, Yousef et al (2019) reported that Rhizobium sp.…”
Section: Agronomic Variables Of Both Corn Genotypesmentioning
confidence: 89%
“…Estudos da literatura mostram que os bioinoculantes, juntamente com a contribuição do fertilizante químico, resultam em um aumento no diâmetro do caule da planta (Xiu, 2014;Zulueta-Rodríguez et al, 2020). Um efeito benéfico foi encontrado no crescimento da parte aérea e das raízes, bem como no colo da raiz e diâmetro do caule de plantas de milho quando inoculadas com cepas de T. harzianum (Okoth et al, 2011).…”
Section: Diâmetro Do Colmounclassified